2018
DOI: 10.5217/ir.2018.16.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of once daily multimatrix mesalazine 2.4 g/day and 4.8 g/day with other 5-aminosalicylic acid preparation in active ulcerative colitis: a randomized, double-blind study

Abstract: Background/AimsThis study compared the efficacy of multimatrix mesalazine 2.4 g/day and 4.8 g/day with controlled-release mesalazine 2.25 g/day.MethodsIn this multicenter, randomized, double-blind study, 251 patients with mildly to moderately active ulcerative colitis received multimatrix mesalazine 2.4 g/day once daily (Multimatrix-2.4), 4.8 g/day once daily (Multimatrix-4.8), or controlled-release (time-dependent) mesalazine 2.25 g/day 3 times daily (Time-2.25) for 8 weeks. The primary efficacy endpoint was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…These results of the study by Ogata et al 6 were similar to that of a recent meta-analysis. 7 The meta-analysis demonstrated that 50% of patients who received 5-ASA failed to achieve remission compared to 52% of patients who received 5-ASA comparator (RR, 0.94; 95% CI, 0.86–1.02).…”
supporting
confidence: 88%
See 3 more Smart Citations
“…These results of the study by Ogata et al 6 were similar to that of a recent meta-analysis. 7 The meta-analysis demonstrated that 50% of patients who received 5-ASA failed to achieve remission compared to 52% of patients who received 5-ASA comparator (RR, 0.94; 95% CI, 0.86–1.02).…”
supporting
confidence: 88%
“…Unlike the study by Ogata et al, 6 the meta-analysis did not assess the significant difference in efficacy between the two 5-ASA dosing regimens (4.8 g/day vs. 2.4 g/day), including pH-release and MMX mesalazines. 7 However, similar to the present study, 6 subgroup analysis of several studies demonstrated that patients with moderate UC might benefit from the high dose of mesalazine (4.8 g/day). 7 8 9 This indicates that the severity of disease can be a factor that affects the response to 5-ASA treatment.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…However, studies with fair comparisons are scarce because the doses of comparative mesalazine formulations are sometimes different (e.g., 2.25 g/day of Pentasa vs. 3.6 g/day of Asacol). Notably, in the few studies using similar doses of different types of mesalazine formulation (3 g/day of pH-dependent mesalazine vs. 3 g/day of time-dependent mesalazine [9] and 2.4 g/day of MMX mesalazine vs. 2.25 g/day of time-dependent mesalazine [10]), an equivalent efficacy and safety were observed in mild to moderately active UC patients.…”
Section: Introductionmentioning
confidence: 99%